Model Alternatif Kelembagaan Partisipatif Program Penanganan Pengurasan Ternak Sapi Betina Produktif Propinsi Jambi - Novra, Ardi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The general objective was to design an institutional alternative model that is more participatory that can function efficiently and effectively in the prevention of slaughtering and selling productive cows.  Research method was a survey by the institutional model of participatory approaches(Participatory Rural Appraisal/ PRA).  Random sampling was undertaken using technique of multistage group (Random multistage cluster sampling).  Processing and tabulation of data using Microsoft excel.  Method of analysis using a simple mathematical approach and descriptive analysis was used in this study.  Based on the research results can be concluded that 1) the public interest to maintain highrelative productive cows and sell them only done on urgent conditions.  2) Program productive handlingof depleted cows can be done through a variety of alternative points but more effective done at household.  3) Strengthening institutional of cattle groups need to be supported by strengthening the financingcapacity of groups such as LKM.